Digital Mediation of Spiritual Experiences: Sense-Making Through Story Completion - Rosa, Jean C. S.; Lopes, Whendell M. C.; Arruda, Isabela L.; Wolf, Sara (Anais da Conferência Latino-Americana de Interação Humano-Computador (CLIHC); 2026: Anais da XII Conferência Latino-Americana de Interação Humano-ComputadorDO - 10.5753/clihc.2026.20278, 2026)
The ubiquity of digital technologies has reconfigured the boundaries between the sacred and the secular, fostering the emergence of technospirituality. In Brazil, this phenomenon is particularly evident among the Evangelical population, which adopts digital artifacts amidst the tensions of the “attention economy”. This paper investigates how believers in the state of Sergipe construct meanings regarding this digital mediation. Methodologically, we advance Human-Computer Interaction (HCI) by leveraging Story Completion complemented by Reflexive Thematic Analysis and Story Mapping. Results reveal that technological adoption is not a binary event but a hermeneutic-pragmatic process that evolves from moral hesitation to conditioned acceptance through user discernment. We suggest that apps function as material substrates that expand interpretative capabilities while reconfiguring spatial and temporal barriers of faith. This work contributes to the field by empirically modeling faith-based sense-making in the Brazil and validating story completion as a robust methodological lens for investigating moral negotiations and subjective meaning-making beyond the limitations of direct self-report.